2012
DOI: 10.1002/jhm.1905
|View full text |Cite
|
Sign up to set email alerts
|

Results of a retrospective observational study of intermediate care staffed by hospitalists: Impact on mortality, co‐management, and teaching

Abstract: An ImCU led by hospitalists showed encouraging results regarding patient survival and SAPS II is an useful tool for prognostic evaluation in this population. Intermediate care serves as an expansion of role for hospitalists; and clinicians, trainees and patients may benefit from co-management and teaching opportunities at this unique level of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 26 publications
2
19
1
Order By: Relevance
“…Multiple studies support the assertion that IMCUs reduce cost without negatively affecting outcomes. 1,10,12,18,19 Although no definitive study exists in either adult or pediatric medical literature, results from our study support that IMCUs identified in this study care for patients who would often be triaged to an ICU at institutions with no IMCU. True cost implications of this variation in triage would require further study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Multiple studies support the assertion that IMCUs reduce cost without negatively affecting outcomes. 1,10,12,18,19 Although no definitive study exists in either adult or pediatric medical literature, results from our study support that IMCUs identified in this study care for patients who would often be triaged to an ICU at institutions with no IMCU. True cost implications of this variation in triage would require further study.…”
Section: Discussionsupporting
confidence: 62%
“…This is in keeping with data from adult literature that support the role of the IMCU in improving ICU utilization for sicker patients. [9][10][11][12] In particular, Byrick et al 13,14 described the impact of closure of an IMCU in 1 hospital, resulting in a fourfold increase in ICU admissions with a lower severity of illness. More recent literature describes successful care for adult patients with specific diseases in IMCUs, including severe asthma and sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Although intermediate care is worldwide recognized, there are few studies in the last decades demonstrating the efficacy of these areas [3-12]. Moreover, there are only two previous descriptions of SAPS II in this setting [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…At present hospitalists on staffs reach 50,000 physicians, more than cardiologists, in almost all medical centers in US [9][10][11][12]. The advantages of HOS include a more rapid, effective and precise dealing with problems no matter in diagnoses, prescription of medications, therapeutic strategies or the communications with patients by sharing decision making with attending physicians rather than by residency in advance [13,14]. Several studies have reported that HOS model at wards provides shorter length of stay and improves quality of care [11,[14][15][16].…”
Section: Application Of Integrated Medicalmentioning
confidence: 99%